THE EFFECTIVENESS OF USING DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMP SWADHARMA MOPUGAD - Kurniyanti, Ni Ketut; Oroh, Elisabeth Z.; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to find out whether Directed Reading Thinking Activity (DRTA) Strategy is effective in teaching reading comprehension in class VIII of Swadharma Mopugad Junior High School. The DRTA (Directed Reading Thinking Activity) reading strategy is a direct reading and thinking strategy, so that students can focus on the text and predict the content of the story by proving it while reading. The researcher used quantitative research method through pre-experimental design with one group pre-test and post-test design and the sample of this research was students of class VIII B SMP Swadharma Mopugad consisting of 28 students. The research instrument used in this study was a multiple choice test. Based on the results of the pre-test and post-test in class VIII B, the average during the pre-test was 46.79 with an achievement of 46.79%, while the average during the post-test increased to 87.68 with an achievement of 87.68% or reached 88%. The mean value for the Post Test is in the score interval 81-100 which is included in the Very High category. The increase in the average score from pre-test to post-test was 40.89 or with a percentage of 40.89%. Based on these data, it can be concluded that the directed Reading Thinking Activity (DRTA) Strategy is effective in improving students' reading comprehension.